(untitled) (Global Journal of Medical Research, 2020)
Ticks are important vector arthropods of human and animal pathogens. Information on tick vectors as well as their distribution in Zaria and environs is very scanty. The study was aimed at identifying the various tick species infesting cattle in Zaria using a molecular technique. Ticks were collected from two hundred cattle (n=200) of which 193 (96.5%) were tick infested. The individual ticks were washed, crushed and incubated at 56°C overnight. The extracted DNA of each sample was extracted and amplified targeting the 16S rRNA portion. Ampl icons were sequenced using a capillary sequencer (ABI PRISMR 3130×1 Genetic Analyzer, Applied Biosystems). All sequences were subjected to a Basic Local Alignment Search Tool (BLAST) to determine their identities and assess their homologues and similarities to those in the Gen Bank.